Consumption of fish and vascular risk factors: A systematic review and meta-analysis of intervention studies. (November 2017) - Alhassan, Abeer; Young, Julie; Lean, Michael E.J.; Lara, Jose
Abstract: Background and aims: Epidemiological evidence of the beneficial health effects of fish consumption is strong, but the evidence from intervention trials is less documented. Our aim was to evaluate the state of the evidence on the potential effects of fish consumption on vascular risk factors arising from intervention trials. Methods: A systematic literature search was undertaken in OVID MEDLINE, Scopus, and EMBASE, which were searched from inception to June 2017. A meta-analysis of intervention trials was performed to estimate the effect of fish consumption on vascular risk factors in adults (age >18 years). Primary outcomes included lipid biomarkers such as triglycerides, total cholesterol, HDL cholesterol and LDL cholesterol, and also novel biomarkers of vascular risk. Secondary outcomes were related to feasibility and acceptability aspects of these interventions. Random-effects models were used to determine the pooled effect sizes. Results: 14 trials, including a total of 1378 individuals, fulfilled the inclusion criteria for this study. Consuming oily fish was associated with significant reductions in plasma triglycerides (−0.11 mmol/L; 95% CI -0.18 to −0.04; p  = 0.002). While a significant increase in HDL-cholesterol was observed (0.06 mmol/L, 95% CI 0.02 to −0.11; p  = 0.008). No significant effect could be observed on other vascular risk factors. Conclusions: This study showed that there is evidence indicating that consuming oily fish led to significant improvements in two important biomarkers of cardiovascular risk, such as triglycerides and HDL levels. These results strongly support the important role for oily fish as part of a healthy diet. Highlights: Consuming oily fish is associated with beneficial effects to health. Current evidence from intervention trials indicates that consuming fish significantly improves some blood lipids, blood pressure and endothelial function. Fish consumption may potentially reduce the risk of cardiovascular diseases and mortality. The effects of consuming fish on novel biomarkers of vascular risk needs further investigation.